From a loser's point of view communicating electoral defeat - Cabal, Ryszelle Ivy M. 1991- (2012)
"This study explored the phenomenon of electoral defeat and communication strategies employed by defeated candidates after an election loss experience. Specifically, this study focused on affective and behavioral responses of defeated candidates toward election loss, and how these responses were communicated to social contact networks and the public. Interviews with 15 defeated candidates were conducted. Ten of the informants belong to the college and university level elections; while three were from barangay level, and two were from the local level elections. Our use of narrative analysis as a mechanism to analyze their stories showed that defeated candidates, across all levels have common experiences in the 1) decision-making, 2) experiencing defeat, and 3) accepting loss processes. They also experiences a wide array of emotions, both negative and positive, toward election loss. Moreover, this study showed that defeated candidates engage in a process called selective disclosure wherein only a portion of all the defeat-related private experiences of a defeated candidate is imparted to their networks. Lastly, this study found out that there are four functions of defeat communication, namely 1) the release function, 2) normalcy, 3) saving face, which explains the motivations of defeated candidates when engaging in specific communicative behaviors in response to defeat."